Low Equality for Women, Slower Economic Growth for All? Evidence from D-8 Countries - Samuda, Sri Juli Asdiyanti (Muslim Business and Economics Review, 2023)
Gender equality promotes economic improvement and reduces income inequality. Considering the goal of all countries to achieve faster and stronger economic growth, improving gender equality may represent a promising solution. This paper examines the link between gender equality and economic growth in the ‘Developing Eight’ (D-8) countries from 1998 to 2021. This study provides estimation using a system GMM and panel causality test to determine the effect of gender equality on economic growth. The results indicate a positive and significant effect of gender equality on economic output in D-8 countries. Heterogenous panel non-causality findings suggest that gender equality and economic output have a bidirectional relationship in D-8 countries, indicating that economic output also affects gender equality.